A Review of Institutional Arrangements for Road Asset Management : Lessons for the Developing World - Queiroz, Cesar; Kerali, Henry (World Bank, Washington, DC, 2014)
The type of institutional arrangement for managing roads adopted by a country depends on the objectives and performance that it sets for its road networks. This paper reviews such arrangements for selected countries; China, Brazil, Slovenia, New Zealand, United Kingdom, and the Slovak Republic. These countries have adopted different approaches in several dimensions, such as decentralization, sources of financing, management structure, and modal responsibility. This paper reviews main factors affecting the efficiency of road agencies and describes the steps taken in creating a new institution, or transforming an existing one, and assesses the effort required to achieve such results. In all countries reviewed, the ministry responsible for the transport sector remains the authority responsible for the overall transport policy and for putting in place checks and balances for good governance and management of fiscal risk. The main aspects of institutional reforms that can contribute to increase the efficiency of road and transport agencies include: improved institutional structures, separation of the client and supplier functions, separation of client and supplier organizations, privatization of the supplier organizations, establishment of an executive agency or a commercialized (client) organization, user participation through oversight boards, improving management information systems, and seeking additional sources of financing.